Resveratrol inhibits invasion and metastasis of colorectal cancer cells via MALAT1 mediated Wnt/β-catenin signal pathway. - Qing Ji; Xuan Liu; Xiaoling Fu; Long Zhang; Hua Sui; Lihong Zhou; Jian Sun; Jianfeng Cai; Jianmin Qin; Jianlin Ren; Qi Li (PLoS ONE)
Resveratrol, extracted from Chinese herbal medicine Polygonum cuspidatum, is known to inhibit invasion and metastasis of human colorectal cancer (CRC), in which long non-coding Metastasis Associated Lung Adenocarcinoma Transcript 1 (RNA-MALAT1) also plays an important role. Using MALAT1 lentiviral shRNA and over-expression constructs in CRC derived cell lines, LoVo and HCT116, we demonstrated that the anti-tumor effects of resveratrol on CRC are through inhibiting Wnt/β-catenin signaling, thus the expression of its target genes such as c-Myc, MMP-7, as well as the expression of MALAT1. In detail, resveratrol down-regulates MALAT1, resulting in decreased nuclear localization of β-catenin thus attenuated Wnt/β-catenin signaling, which leads to the inhibition of CRC invasion and metastasis. This finding of ours surely provides important pre-clinical evidence supporting future use of resveratrol in prevention and treatment of CRC.